Modern encyclopaedia of women and development - Mahapatra, Subhasini (New Delhi, India : Rajai Publications, 2005)
v. 5 Reflections on crime against women
v. 4 Women welfare : issues and challenges
Keywords: Women -- Encyclopedias; Women in development